TH17 Cell Frequency in Peripheral Blood Is Elevated in Overweight Children without Chronic Inflammatory Diseases - Schindler, Theresa Isabell; Wagner, Johanna-Josophina; Goedicke-Fritz, Sybelle; Rogosch, Tobias; Coccejus, Verena; Laudenbach, Verena; Nikolaizik, Wilfried; Härtel, Christoph; Maier, Rolf Felix; Kerzel, Sebastian; Zemlin, Michael (Frontiers in Immunology, 2017)
Background: The prevalence of obesity has dramatically increased in children in the last few decades and is associated with chronic inflammatory diseases. Fat tissue produces IL-6 and TNF-α, which are stimuli for TH17 cell differentiation. These cells are characterized by expression of the transcription factor RORC and by IL-17A production. In murine models, obesity has been linked with elevated TH17 cell frequencies. The aim of this study was to explore whether being overweight was associated with an elevated frequency of circulating TH17 cells or elevated mRNA-levels of IL-17A and RORC in children without chronic inflammatory diseases. Methods: We studied peripheral blood samples from 15 overweight and 50 non-overweight children without a history of autoimmune diseases, asthma, atopic dermatitis or allergic rhinoconjunctivitis. TH17 cells were quantified in Ionomycin stimulated peripheral blood mononuclear cells by flow cytometry using intracellular IL-17A staining. RORC- and IL-17A expressions were measured by real-time PCR. Results: We found significantly elevated TH cell frequencies in overweight children compared the non-overweight controls with 34.7 ± 1.5 % of CD3+CD4+ cells versus 25.4 ± 2.4 % (mean ± SEM, p = 0.0023), respectively. Moreover, TH cell frequencies correlated positively with body mass index (r = 0.42, p = 0.0005, respectively). The relative mRNA expression of RORC (p= 0.013) and IL-17A (p= 0.014) were upregulated in overweight compared to non-overweight children. Conclusions: Childhood obesity is an independent factor that is associated with an elevated frequency of circulating TH17 cells and higher expression of RORC- and IL-17A-mRNA after in-vitro stimulation with Ionomycin. This might be due to the inflammatory activity of the fat tissue. Studies on TH17 immunity should not only be adjusted for acute and chronic inflammatory diseases but also for overweight.